2017 IEEE Global Engineering Education Conference (EDUCON) 2017
DOI: 10.1109/educon.2017.7942879
|View full text |Cite
|
Sign up to set email alerts
|

Improving student engagement in higher education through mobile-based interactive teaching model using socrative

Abstract: Abstract-One of the main problem in higher education teaching is low students' levels of engagement leading to poor learning performance. Broad teaching strategies, methods and tools are developed over the years to address this concern. In recent years, with the increasing numbers of students accessing the internet using mobile devices, there has been growing interest in embracing the mobile technology in teaching to improve the student participation in the classroom. This research describes the design and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 14 publications
5
40
0
6
Order By: Relevance
“…The immediate feedback also likely contributed positively to students' experiences -providing them with the correct answer and information they can use immediately. This is consistent with the use of technology in the classroom and learning materials to provide instant feedback being highly liked and accepted by students (Elmahdi, Al-Hattami, and Fawzi 2018;Liberatore 2017;Lim 2017;Viegas et al 2015). We observed that many students reached out, either through email or the course discussion board, if the explanation did not provide enough clarity.…”
Section: Opinionssupporting
confidence: 69%
“…The immediate feedback also likely contributed positively to students' experiences -providing them with the correct answer and information they can use immediately. This is consistent with the use of technology in the classroom and learning materials to provide instant feedback being highly liked and accepted by students (Elmahdi, Al-Hattami, and Fawzi 2018;Liberatore 2017;Lim 2017;Viegas et al 2015). We observed that many students reached out, either through email or the course discussion board, if the explanation did not provide enough clarity.…”
Section: Opinionssupporting
confidence: 69%
“…SG freshmen answered these quizzes through the student response system (SRS) Socrative, whose use has been widely discussed [93,94] in the implementation of interactive teaching. Coherently to the documented positive results of the Bring Your Own Device (BYOD) strategy [95], the SG students employed their own electronic devices, like laptops, smartphones and tablets.…”
Section: Learning Design and Assessment Toolsmentioning
confidence: 99%
“…Lim [29] presented the design and implementation of a mobile-based interactive teaching model with in-class and off-class components aided by Socrative online response system to improve the engagement of the students in a Malaysian university. Table 1 summarizes the researchbased mobile learning systems from the literature and their limitations.…”
Section: Mobile Learning Solutions In Higher Educationmentioning
confidence: 99%